Exploration of rural physicians’ lived experience of practising outside their usual scope of practice to provide access to essential medical care (clinical courage): an international phenomenological study - David Campbell; Lucie Walters; Jill Konkin; Laura Grave; Ella Cockburn; Ian Couper; Ruth Alison Stewart (BMJ Open)
Objectives Rural doctors describe consistent pressure to provide extended care beyond the limits of their formal training in order to meet the needs of the patients and communities they serve. This study explored the lived experience of rural doctors when they practise outside their usual scope of practice to provide medical care for people who would otherwise not have access to essential clinical services.Design A hermeneutic phenomenological study.Setting An international rural medicine conference.Participants All doctors attending the conference who practised medicine in rural/remote areas in a predominantly English-speaking community were eligible to participate; 27 doctors were recruited.Interventions Semi-structured interviews were conducted. The transcripts were initially read and analysed by individual researchers before they were read aloud to the group to explore meanings more fully. Two researchers then reviewed the transcripts to develop the results section which was then rechecked by the broader group.Primary outcome measure An understanding of the lived experiences of clinical courage.Results Participants provided in-depth descriptions of experiences we have termed clinical courage. This phenomenon included the following features: Standing up to serve anybody and everybody in the community; Accepting uncertainty and persistently seeking to prepare; Deliberately understanding and marshalling resources in the context; Humbly seeking to know one’s own limits; Clearing the cognitive hurdle when something needs to be done for your patient; Collegial support to stand up again.Conclusion This study elucidated six features of the phenomenon of clinical courage through the narratives of the lived experience of rural generalist doctors.